Advances in Treponema denticola and oral diseases - PENG Ruiting; CHENG Lei; PENG Xian (口腔疾病防治, 2020)
Treponema denticola is an important pathogenic Treponema pathogen in the human oral cavity. Early studies have found that Treponema denticola is closely related to the occurrence and development of periodontal diseases. With the development of technical methods in recent years, many studies have shown that Treponema denticola not only can participate in periodontal diseases through a variety of mechanisms but also can play an important role in the development of various oral diseases. Treponema denticola is detected in high concentrations in peri-apical diseases and peri-implant diseases, and its surface protein is also prevalent in oral tumor samples. This paper reviews the research progress of Treponema denticola in periodontal diseases, pulp peri-apical diseases, peri-implant diseases and oral tumors, and summarizes the relevant mechanisms. For example, Treponema denticola can cause immune regulation disorder, destroy the epithelial barrier, induce bone absorption, promote the occurrence and development of inflammation through a variety of surface proteins, including chymotrypsin-like protease complex (CTLP), major outer sheath protein (Mosp), Td92, and LOS. It can also escape complement-mediated killing effects through surface FhbB lipoproteins and promote the occurrence and development of oral tumors by regulating the tumor microenvironment. These theories provide a theoretical basis for further understanding the development of oral diseases, controlling the infection of Treponema denticola, and exploring more effective treatment strategies.